A camouflaging mystery: solid-tubulocystic variant of intrahepatic cholangiocarcinoma - Zhang, Shannon; Hasan, Nazmul; Han, John; Kroening, Gianna; Jutric, Zeljka; Afsari, Ali; Attarian, Shirin; Valerin, Jennifer (Human Pathology Reports, 2025)
[Display omitted] •Solid-tubulocystic variant of iCCA presents in young patients without risk factors.•This variant exhibits NIPBL-NACC1 gene fusion with distinct biphasic histology.•Inhibin and synaptophysin may lead to misdiagnosis as neuroendocrine tumor.•Limited immunotherapy response despite high TMB; PD-L1 and MSI-H are not predictive.•Molecular testing in rare iCCA variants is crucial to avoid diagnostic pitfalls. Cholangiocarcinoma is a rare and aggressive malignancy with a rising incidence in recent years. Known risk factors include cirrhosis, alcohol use, smoking history, family history of bile duct cancer, male gender, and hepatitis B and/or C. The solid-tubulocystic variant of intrahepatic cholangiocarcinoma, previously named cholangioblastic variant, is an even rarer form with only several cases reported in literature to date. Interestingly, this variant is not associated with the same risk factors as typical cholangiocarcinoma, often diagnosed in young, previously healthy females. Given its rarity, diagnosis is often delayed and optimal treatment is unknown, leading to poor prognosis. Here, we discuss the case of an 18-year-old female admitted to our hospital with solid-tubulocystic variant of cholangiocarcinoma, in which molecular analysis confirmed the presence of a characteristic NIPBL-NACC1 gene rearrangement, and our management.